Production regions and physical quality of Urochloa decumbens CV. Basilisk seeds (Bioscience Journal, 2019)
Brazil is the largest world producer, consumer and exporter of forage grass seeds. Urochloa decumbens Stapf. species is the second in importance in the Brazilian market of seeds of tropical forage grasses. Seeds are harvested by the soil sweeping method and, in addition to other impurities, harvested lots can present weed seeds, which makes seeds unfeasible for commercialization. The aim of the present study was to evaluate differences in the physical quality and viability of Urochloa decumbens cv. Basilisk seeds produced in different production fields. Fifteen U. decumbens seed lots from the State of São Paulo (1 lot in the municipality of Cássia dos Coqueiros and 3 lots in the municipality of Santo Antônio da Alegria), Minas Gerais (2 lots in the municipality of Tupaciguara, 2 lots in the municipality of Unaí, 2 lots in the municipality of Chapada Gaúcha and 3 lots in the municipality of Monte Santo de Minas), Goiás (1 lot in the municipality of Jataí) and Mato Grosso (1 lot in the municipality of Primavera do Leste) were evaluated by means of the following parameters: water content, viability by tetrazolium test, purity, determination of other seeds by number and weight of one thousand seeds. A completely randomized design was used, and when significant, the means of treatments were compared by the Scott Knott test at 5% probability. The fields of the different regions produce U. decumbens seeds with high variability in physical quality. U. decumbens seeds with the highest physical quality and viability were produced in Cassia dos Coqueiros - SP.